Exemption from Criminal Liability for Inappropriate Use of Public Funds with Court Fining - Kulii L. A., Kozyr G. I. (Interactive science, 2020)
the issue of exemption from criminal liability based on specific elements of a crime is relevant to an array of crimes. The exemption with court fining is relatively new in the criminal law. Considering the peculiarity of dispositions of the articles 285.1, 285.2 of the Criminal Code of Russia the establishment of the application of the fine for specific crimes remains dubious. The present issue is not covered sufficiently in the theory of the criminal law. Based on scientific researches and case law, specific problems involved in the implementation of the article 72.2 in relation to inappropriate use of public and state non-budgetary funds are established in the present article.
Keywords: бюджетные средства; государственные внебюджетные фонды; судебный штраф; нецелевое расходование; освобождение от уголовной ответственности; exemption from criminal liability; court fine; inappropriate use; public funds; state non-budgetary funds